PAI-1 haplogenotype confers genetic susceptibility for obesity and hypertriglyceridemia in Mexican children. - de la Cruz-Mosso, Ulises; Ramos-Arellano, Luz Elena; Muñoz-Valle, José Francisco; Salgado-Bernabé, Aralia Berenice; Salgado-Goytia, Lorenzo; Castro-Alarcón, Natividad; Ramírez-Peralta, Arturo (Investigación Clínica, 2016)
Ver Resuemen PDF.